2010
DOI: 10.3390/ijerph7052423
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Information Systems (GIS) in Assessing Dental Health

Abstract: The present study investigated the distribution profile of dental caries and its association with areas of social deprivation at the individual and contextual level. The cluster sample consisted of 1,002 12-year-old schoolchildren from Piracicaba, SP, Brazil. The DMFT Index was used for dental caries and the Care Index was used to determine access to dental services. On the individual level, variables were associated with a better oral status. On the contextual level, areas were not associated with oral status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
(22 reference statements)
2
29
0
3
Order By: Relevance
“…Research indicates that the earliest disease maps were found in Germany over 200 years ago [13]. Over time, the use of GIS has emerged in the field of disease surveillance [14], linking correlations to health, environment, and location [13,15], in addition to informing longitudinal studies [14,16]. Nykiforuk and Flaman [17] have identified four major themes in health GIS: disease surveillance, risk analysis, health access and planning, and community health profiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that the earliest disease maps were found in Germany over 200 years ago [13]. Over time, the use of GIS has emerged in the field of disease surveillance [14], linking correlations to health, environment, and location [13,15], in addition to informing longitudinal studies [14,16]. Nykiforuk and Flaman [17] have identified four major themes in health GIS: disease surveillance, risk analysis, health access and planning, and community health profiling.…”
Section: Introductionmentioning
confidence: 99%
“…The field of urban planning and health is among the first in policy analysis through GIS, for example through the design of health impact and health risk assessments, integrating GIS to determine how policy will affect populations in urban space [18,19]. GIS has also been an aid to understanding the relationship between health and the environment as a facilitator of a "continuous process of planning, monitoring, and evaluating health", allowing for a quick identification of locations where there are health problems at a greater frequency [15]. As a result, health policy benefits from the use of GIS through the analysis and visualization of data in geographic format.…”
Section: Introductionmentioning
confidence: 99%
“…Factors addressed by health geography studies investigating the dynamics of dental health disparities include the following: the geographical distribution of dental professionals 14,15,16,17 ; variables representing socioeconomic status 18,19,20,21,22,23 ; and lifestyle behaviors associated with poor oral health, such as consumption of sugared beverages and dental attendance patterns 16,24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have been limited to contrasts between rural and urban environments and little research has been carried out into the geographical factors that influence access to dental care and the prevalence of oral conditions 16,20,23,25,26,27,28,29 . Although some Brazilian and Australian studies have investigated geographical barriers 22,23,26,27 , we believe that there is still a lack of comprehensive research into these factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation